2022
DOI: 10.3389/fpls.2022.846720
|View full text |Cite
|
Sign up to set email alerts
|

Mixture × Genotype Effects in Cereal/Legume Intercropping

Abstract: Cropping system diversification through annual intercropping provides a pathway for agricultural production with reduced inputs of fertilizer and pesticides. While several studies have shown that intercrop performance depends on the genotypes used, the available evidence has not been synthesized in an overarching analysis. Here, we review the effects of genotypes in cereal/legume intercropping systems, showing how genotype choice affects mixture performance. Furthermore, we discuss the mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…It is also not likely that current varieties are already optimally suited for intercropping ( 54 , 65 , 66 ). Research is needed to elucidate whether and how the performance of intercropping systems may be further optimized by breeding “plant teams” that optimize complementary resource capture ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also not likely that current varieties are already optimally suited for intercropping ( 54 , 65 , 66 ). Research is needed to elucidate whether and how the performance of intercropping systems may be further optimized by breeding “plant teams” that optimize complementary resource capture ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it has been reported that the performance in sole crop could not be considered as an index of wheat performance in mixed cropping (Kammoun et al, 2021;Tavoletti & Merletti, 2022). The nal performance of intercropping depends on the combination of competition, complementarity, cooperation, and compensation between the species which has been named as "The 4C approach" (Demie et al, 2022;Justes et al, 2021). Therefore, the best cultivars for sole cropping are not necessarily the best ones for intercropping.…”
Section: Dependence Mixture On Cultivar Identity Environment and Densitymentioning
confidence: 99%
“…The cereal-legume intercropping system is an archetypal example of diversification. It provides a quantitative dry matter yield equivalent to that produced by these two pure crops, while increasing protein yield and reducing nitrogen fertilization requirements [5][6][7]. The objective of the intercropping is to link two nutritionally and morphologically complementary crops.…”
Section: Introductionmentioning
confidence: 99%